1995
DOI: 10.1200/jco.1995.13.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel is a major cytotoxic drug for the treatment of advanced breast cancer: a phase II trial of the Clinical Screening Cooperative Group of the European Organization for Research and Treatment of Cancer.

Abstract: Our data suggest that docetaxel has major antitumor activity when used as a single cytotoxic agent as first-line chemotherapy in advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
61
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(64 citation statements)
references
References 15 publications
2
61
1
Order By: Relevance
“…Based on these phase I studies, the recommended singleagent dose and schedule for docetaxel was 100 mg m-2 given as a 1-h infusion every 3 weeks. Phase II studies on docetaxel showed activity in breast cancer (Seidman et al, 1993;Ten Bokkel-Huinink et al, 1994;Trudeau et al, 1993;Valero et al, 1993;Chevallier et al, 1995), non-small-cell lung cancer (Cemy et al, 1994;Fossella et al, Rotterdam, Groene Hilledijk 301, 3075 EA Rotterdam, The Netherlands 1995; Miller et al, 1995), head and neck cancer , gastric cancer (Sulkes et al, 1994), melanoma (Aamdal et al, 1994), soft tissue sarcoma (Van Hoesel et al, 1994) and pancreatic cancer (De Fomi et al, 1994). The most important side-effect was an early and short-lasting neutropenia, which in 20% of the patients was complicated by infection (Pronk et al, 1995).…”
mentioning
confidence: 99%
“…Based on these phase I studies, the recommended singleagent dose and schedule for docetaxel was 100 mg m-2 given as a 1-h infusion every 3 weeks. Phase II studies on docetaxel showed activity in breast cancer (Seidman et al, 1993;Ten Bokkel-Huinink et al, 1994;Trudeau et al, 1993;Valero et al, 1993;Chevallier et al, 1995), non-small-cell lung cancer (Cemy et al, 1994;Fossella et al, Rotterdam, Groene Hilledijk 301, 3075 EA Rotterdam, The Netherlands 1995; Miller et al, 1995), head and neck cancer , gastric cancer (Sulkes et al, 1994), melanoma (Aamdal et al, 1994), soft tissue sarcoma (Van Hoesel et al, 1994) and pancreatic cancer (De Fomi et al, 1994). The most important side-effect was an early and short-lasting neutropenia, which in 20% of the patients was complicated by infection (Pronk et al, 1995).…”
mentioning
confidence: 99%
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).Peripheral neurotoxicity has been reported as a frequent, but usually mild side-effect of docetaxel in several phase I and phase II studies (Bissett et al, 1993;Extra et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995; Hilkens et al, 1996;New et al, 1996). The neurotoxic effects of docetaxel in combination Chemotherapy was administered in 3-weekly regimens.…”
mentioning
confidence: 75%
“…Significant correlations were present between both the cumulative dose of docetaxel and cisplatin and the post-treatment sum-score of neuropathy (P < 0.01) as well as the post-treatment VPT (P < 0.01). The neurotoxic effects of this combination were more severe than either cisplatin or docetaxel as single agent at similar doses.Keywords: neuropathy; docetaxel; cisplatin; neurotoxicity; peripheral nerves; chemotherapy Docetaxel (Taxotere) is a new semisynthetic taxoid that has demonstrated substantial clinical activity against a wide variety of solid tumours (Pazdur et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995). Docetaxel inhibits tubulin depolymerization and promotes microtubule assembly, resulting in dysfunctional microtubules (Pazdur et al, 1993).…”
mentioning
confidence: 99%
See 2 more Smart Citations